THE EFFECT OF SELF EFFICACY ON SELF REGULATED LEARNING AMONG STUDENTS OF STATE ISLAMIC UNIVERSITY DURING ONLINE LEARNING: self efficacy dan self regulated learning pada mahasiswa Islam - Paulina, Melisa; Mutiah, Diana; Panaemalae, Abdul Razak Abdulroya (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to learn the effect of self-efficacy on self-regulated learning during online learning for Islamic students. The sampling technique used was purposive sampling, with a total sample of 410 Raden Fatah State Islamic University (UIN) Palembang students. The results showed that the relationship or the value of the correlation coefficient between the variables of self-efficacy and self-regulated learning was 0.466. The significance value is 0.0019 where (p<0.05') then (sig='0.001<0.05) and the results of hypothesis testing are known that the results of the R-square test of the self-efficacy variable on self-regulated learning are 0.217. These results indicate that 21.7% of self-efficacy affects self-regulated learning variables. Thus, self-efficacy and self-regulated learning have a significant positive effect on Islamic students at the Raden Fatah State Islamic University (UIN) Palembang. In other terms, the higher the self-efficacy, the higher the level of self-regulated learning.